Cellular automata-based authentication for low-cost RFID systems. (29th June 2009) - Tripathy, S.; Nandi, S.
Radio frequency identification (RFID) tags can be affixed with every item to identify the objects without any visual or physical contact. At the same time, the use of the tags can have serious implications on new risks to security and privacy. Also, it is difficult to implement the cryptographic mechanisms into low-cost RFID tags. In this paper, we propose a cellular automata-based authentication mechanism suitable for low-cost RFID systems.